PENERAPAN PANJANG TALANG DAN JARAK TANAM DENGAN SISTEM HIDROPONIK NFT (Nutrient Film Technique) PADA TANAMAN KAILAN (Brassica oleraceae var. alboglabra) - Daviv Zali Vidianto; Siti Fatimah; Catur Wasonowati (Agrovigor, 2013)
Kailan vegetables is one kind of high economic value that can be grown in hydroponic NFT (Nutrient Film Technique). The purpose of this study to determine the effect of chamfer length and spacing of the system hydroponic NFT (Nutrient Film Technique) on the growth and yield kailan (Brassica oleraceae var. Alboglabra). The research has been done in the greenhouse of the Faculty of Agriculture, University Department Agroekoteknologi Trunojoyo Madura District Kamal village Telang Bangkalan. Tat is was conducted in February-May 2012. Research using methods completely randomized design (CRD) with non factorial treatment chamfer length 2 m with spacing of 15 cm (P1J1), chamfer length 2 m with spacing of 20 cm (P1J2), chamfer length of 4 m with spacing of 15 cm (P2J1 ) and chamfer length of 4 m with spacing of 20 cm (P2J2). The materials used are kailan seeds, fertilizers and hydroponics Goodplant acetic acid (CH3COOH). Observations were analyzed using analysis of variance and Duncan continued Test Distance (UJD) level of 5%. P1J1 (chamfer length of 2 meters and 15 cm plant spacing) gives the best effect on the variable root length, number of leaves and plant canopy wet weight. The treatment does’n effect to variable leaf area, root wet weight, dry weight, and root dry weight of the plant canopyKeyword : Brassica oleraceae var. Alboglabra, hydroponik NFT, chamfer length and spacing